Decision Support System of Menu Selection Using Topsis Method at Saung Oshin Restaurant - Musa’Adah Musa’Adah; Adiyanto Adiyanto; Masduki Asbari (UJoST- Universal Journal of Science and Technology, 2022)
- Food is one of the main needs of human life, with the development of the times, food with various kinds of processing innovations can be easily found everywhere. But sometimes there is an over choice or choice overload situation, where the visitor is confused about what food to order because of the many available food menus and the mood of the visitor who doesn't want to eat anything. Overchoice or choice overload is a cognitive process in which people have difficulty making decisions because there are too many choices. The method used in the decision-making process is TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) which is a multi-criteria decision making where the best alternative has the longest distance from the negative ideal solution and the shortest distance from the positive ideal solution. From the results of the research that has been carried out, it produces a decision support system with the TOPSIS method (Technique for Order Preference by Similarity to Ideal Solution) and also the calculation of the system that was built to produce a ranking from the largest preventive value to the smallest.